PROFIL KADAR C-Reactive Protein (CRP), Rheumatoid Factor (RF) DAN LIMFOSIT SEBAGAI INDIKATOR RESPON IMUNITAS PADA LANSIA - Yusuf Eko Nugroho; Meka Faisal Farabi; Anintya Dwi Marrena (LPPM Universitas Abdurrab, 2023)
C-Reactive Protein (CRP) is an acute phase protein that is present in normal serum in very small amounts. There are many factors that can affect CRP levels including age, gender, and smoking status. Increasing age allows the emergence of several groups of rheumatic diseases. One of the rheumatism groups that often accompanies the elderly is Rheumatoid Arthritis (RA). Elderly is an age that has a greater chance of experiencing autoimmunity. RA sufferers in the elderly around the world have reached 355 million people, meaning that 1 in 6 elderly people in the world suffer from rheumatism. The resulting human immune response depends on lymphocytes, where systemic inflammation significantly suppresses cellular immunity. Based on the Central Java Health Profile (2019) it shows that the number of elderly people in Cilacap Regency is 174,143 people. This study aims to analyze the number of lymphocytes as an indicator of the immune response in the elderly against levels of CRP, RF. The method used is descriptive qualitative method. From the results of a study of 30 samples in residents of RW 03, Donan Cilacap Village, the results of qualitative examination of CRP and RF levels showed normal results (100%), and the lymphocyte count results obtained for a number of 12 samples showed low results.